Research progress on the association of estrogen and progesterone with condyloma acuminatum - Bing HAN; Han ZHAO; Liqin WANG; Shuyun ZHENG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Condyloma acuminatum (CA) is a sexually transmitted disease characterized by proliferative lesions in the anogenital region, and its pathogenesis is mainly related to HPV infection and disturbed immune responses. Studies have shown that the incidence of CA is higher in women than in men, and the incidence of CA during pregnancy is higher than that during non-pregnancy. Sex hormones may be related to the occurrence and development of CA. This article reviews the association of estrogen and progesterone with CA, and discusses the possible link of estrogen and CA to the balance of Th1/Th2 and Th17/Treg in cellular immunity during HPV infection, in addition to exploration of the role of estrogen and progesterone in the pathogenesis and recurrence of CA, in order to provide new ideas for the clinical diagnosis and treatment of CA.